Analysis of Multiple Effects of Sustainable Poverty Alleviation Relying on Endogenous Power during Transitional Period - Ping Li, Zuotie Wang (Forest Chemicals Review, 1970)
To achieve the goal from poverty alleviation to rural revitalization, it is necessary to rely on the endogenous power and take measures of sustainable poverty alleviation. Construct a theoretical model of multiple effects of the endogenous power on sustainable poverty alleviation, and reveal the relationship and operating mechanism. Establish a structural equation model of the relationship between factors of the endogenous power, and get a standardized path for poverty alleviation, furthermore tested the effects based on the development of poverty alleviation counties in Heilongjiang Province. Research shows that the constituent elements of the endogenous power have a traction effect on poverty alleviation, a catalytic effect on stable poverty alleviation, and a leading effect on common prosperity. During the transitional period to achieve the goal of strong, beauty and prosperity on agriculture, rural areas, and farmers, the first is to consolidate the results of poverty alleviation, pay more attention to policy linkage, and maintain the stability of the poverty alleviation object; the second is to expand the results of poverty alleviation, strengthen the connection of motivition, and activate the subject's enthusias; the third is to promote the transition period efficiently, promote the integration of industries, and enhance the integration of poverty alleviation carriers; the fourth is to realize the revitalization of the countryside, improve the planning and connection, and ensure the sustainability of development after poverty alleviation. The first sentence of the Abstract should follow the word “Abstract.” on the same line. The abstract should be clear, descriptive, self-explanatory. It should also be suitable for publication in abstracting services. Do not include references or formulae in the abstract. The first sentence of the Abstract should follow the word “Abstract.” on the same line. The abstract should be clear, descriptive, self-explanatory. It should also be suitable for publication in abstracting services. Do not include references or formulae in the abstract.